Physically active lessons in schools and their impact on physical activity, educational, health and cognition outcomes: a systematic review and meta-analysis. Issue 14 (16th October 2019) - Norris, Emma; van Steen, Tommy; Direito, Artur; Stamatakis, Emmanuel
Abstract : Objective: This review provides the first meta-analysis of the impact of physically active lessons on lesson-time and overall physical activity (PA), as well as health, cognition and educational outcomes. Design: Systematic review and meta-analysis of controlled studies. Six meta-analyses pooled effects on lesson-time PA, overall PA, in-class educational and overall educational outcomes, cognition and health outcomes. Meta-analyses were conducted using the metafor package in R. Risk of bias was assessed using the Cochrane tool for risk of bias. Data sources: PubMed, Embase, PsycINFO, ERIC and Web of Science, grey literature and reference lists were searched in December 2017 and April 2019. Studies eligibility criteria: Physically active lessons compared with a control group in a randomised or non-randomised design, within single component interventions in general school populations. Results: 42 studies (39 in preschool or elementary school settings, 27 randomised controlled trials) were eligible to be included in the systematic review and 37 of them were included across the six meta-analyses (n=12 663). Physically active lessons were found to produce large, significant increases in lesson-time PA ( d =2.33; 95% CI 1.42 to 3.25: k =16) and small, increases on overall PA ( d =0.32; 95% CI 0.18 to 0.46: k =8), large, improvement in lesson-time educational outcomes ( d =0.81; 95% CI 0.47 to 1.14: k =7) and a small improvement in overall educational outcomes ( d =0.36; 95% CI 0.09 to 0.63: k =25). No effects were seen on cognitive (k=3) or health outcomes (k=3). 25/42 studies had high risk of bias in at least two domains. Conclusion: In elementary and preschool settings, when physically active lessons were added into the curriculum they had positive impact on both physical activity and educational outcomes. These findings support policy initiatives encouraging the incorporation of physically active lessons into teaching in elementary and preschool setting. Trial registration number: CRD42017076933.